RISK MANAGEMENT FACTORS AND OPERATIONAL EXCELLENCE IN THE OIL AND GAS SECTOR: A PILOT SURVEY - Muazu Hassan Muazu; Usman Shehu Yahaya (Universitas Pakuan, 2022)
ABSTRACTThis study is aimed at determining the appropriateness of the method and instrument to be used to measure the effect of enterprise risk management determinants and effect on operational excellence, as well as enterprise risk management implementation in the Nigerian oil sector. There are 70 questionnaires were used for the pilot survey analysis via SPSS. The findings further revealed the significant effect of all the risk management factors and implementation except staff capacity on operational excellence from the pilot survey. The article was able to develop a research framework and create, and tested measurement instruments for data collection for the current research and future studies in the area of operational excellence and risk management implementation. The implication of the study is that the importance of risk management in the operational performance of the oil and gas sector is key, it must therefore be prioritized for the achievement of operational excellence.ABSTRAKPenelitian ini bertujuan untuk menentukan kelayakan metode dan instrumen yang akan digunakan untuk mengukur pengaruh determinan dan pengaruh manajemen risiko perusahaan terhadap keunggulan operasional, serta penerapan manajemen risiko perusahaan di sektor minyak Nigeria. Ada 70 kuesioner digunakan untuk analisis survei percontohan melalui SPSS. Temuan lebih lanjut mengungkapkan pengaruh signifikan dari semua faktor dan implementasi manajemen risiko kecuali kapasitas staf pada keunggulan operasional dari survei percontohan. Artikel tersebut mampu mengembangkan kerangka penelitian dan membuat, dan menguji instrumen pengukuran untuk pengumpulan data untuk penelitian saat ini dan studi masa depan di bidang keunggulan operasional dan implementasi manajemen risiko. Implikasi dari kajian ini adalah pentingnya manajemen risiko dalam kinerja operasional sektor migas, oleh karena itu harus diprioritaskan untuk pencapaian operational excellence.